Effect of a Cylindrical Permeable Wall on the Performance of Hydrocyclones. Issue 6 (26th February 2016) - Salvador, Fernanda F.; Barrozo, Marcos A. S.; Vieira, Luiz G. M.
Abstract: Hydrocyclones are designed for solid‐liquid separation widely used in industry due to their advantages including high separation efficiency. Depending on the purpose desired by the user, it is possible to enhance the performance of the hydrocyclone through the combined use of other unit operations with the hydrocycloning such as filtration. The incorporation effect of a porous cylinder on a hydrocyclone with optimized geometry was studied experimentally. According to the main results, the filtering cylindrical hydrocyclone showed significant average reductions in energy consumption compared to conventional hydrocyclones of the same geometry. Minor differences in terms of total efficiency of the filtering equipment were observed compared to the conventional one. Abstract : The performance of a hydrocyclone can be improved by combining it with other operation units. A porous cylindrical wall was incorporated in a conventional hydrocyclone geometry, providing a filtering cylindrical hydrocyclone with lower average energy consumption and high separation efficiency compared to conventional hydrocyclones of the same geometry.